Effects of the ‘musicogram’ on children’s musical perception and learning - Boal-Palheiros, G. (2006)
Learning how to listen to music is important, in order to better understand and appreciate it. Children’s everyday modes of listening are often physically active (i.e. singing, dancing), whereas music teachers generally use more passive approaches. Music pedagogue Jos Wuytack has proposed a strategy for teaching non-musicians (‘Active music listening with the musicogram’), which demands the listener’s both physical and mental participation, before and during the listening activity. Children previously learn the musical materials through performance. They then listen while following a ‘musicogram’, in which musical elements and form are represented through colours, geometric figures and symbols. Empirical observation in schools suggests that this strategy enhances children’s learning and enjoyment of ‘classical’ music. Some studies also indicate the advantages of visual materials to enhance perception of ‘classical’ music in nonmusically trained young people. Although music listening and perception have been extensively researched, specific strategies to teach music listening have got somewhat less attention from researchers. This study investigated the effects of the ‘musicogram’ upon children’s perception and learning of ‘classical’ music. Children from Australia, Belgium and Portugal attended to a lesson taught by the same teacher, in which they listened to the ‘March’ from Tchaikovsky’s ‘Nutcracker Suite’ either with or without the ‘musicogram’. After, they were asked about musical characteristics of the excerpt (form, instruments, and tempo) and their enjoyment for both the music and the lesson.